(untitled) (Nigerian Journal of Technology, 2016)
Previous analysis showed that cavity size and number on one hand and combinations thickness affect the compressive strength of hollow sandcrete blocks. Series arrangement of the cavities is common but parallel arrangement has been recommended. This research performed a comparative analysis of the compressive strength of cavities of different configurations. The test thin plate distributes the load on the block and the hollow block is regarded as a two way slab. The results showed that at equal end-web to centre -web thickness (1:2) and total cavity volume the stresses in the parallel configuration were higher than those in series configuration. The minimum stresses in the series arrangement were lower than the corresponding values in the parallel arrangement. In addition, the maximum stresses in the series arrangement were lower than the corresponding values for parallel arrangement. The implication is that at same volume and number of cavities and web thickness, the series arrangement results induced least stress. http://dx.doi.org/10.4314/njt.v35i2.3